Bone tissue remodelling in the periprosthetic region depending upon the type of the joint stem fixation and the shape of the femoral canal - Filipenko, Volodymyr; Podgayskaya, Olga; Tankut, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Changes of bone tissue density in the periprosthetic region of the femur after total hip arthroplasty with use of different types of fixation (proximal, metaphyseal, distal) of stem components in canals of different shape were analysed. The frequency of development of pathological reconstruction of the bone tissue, namely, stress shielding syndrome and aseptic stem loosening, was studied. It was revealed that in case of the cylindrical shape of the medullary canal the distal and metaphyseal types of stem fixation should be preferred, the proximal and metaphyseal types as well as a short stem being chosen for the conical shape.